Analisis Perhitungan Harga Pokok Produksi Pada Perusahaan Manufaktur Usaha Kecil (Studi Kasus: Perusahaan Cherryka Bakery Yogyakarta) - S. Prasetyo Andre Kristrianto; Yushita Marini (Mahesa Research Center, 2023)
Today, cost accounting practices are needed for manufacturing companies, including companies engaged in bakery, both small and large companies. Cherryka Bakery is a small business manufacturing company in the production of various cakes and breads that calculates the cost of production using an order cost system for each bread order. In practice, where the calculation of the cost of production carried out by Cherryka Bakery only includes elements of direct raw materials and indirect raw materials, so it is considered less relevant to use an order cost system, therefore the author is interested in analyzing the calculation of the cost of production at Cherryka Bakery Yogyakarta. . This research uses qualitative methods on financial data sourced from Cherryka Bakery and field studies in conducting data analysis on the calculation of the cost of production and its application. The results of this study can be concluded that Cherryka Bakery's cost accounting system is still weak, so the authors suggest setting appropriate standard costs. with the needs of the elements of production and non-production costs from the specifications of each product so that it can be more in line with the characteristics of Cherryka Bakery.